Integrasi Perkebunan, Perikanan, dan Peternakan untuk Mewujudkan Rumah Pangan Lestari di Desa Banyu Urip, Lombok Tengah - Dhony Hermanto; Nurul Ismillayli; Muhammad Zakirrahman; Sawmi Jannaturrayyan; Lalu Agung Nartiadi (Jurnal Pengabdian Pada Masyarakat, 2020)
INTEGRATION OF PLANTATION, FISHERIES, AND LIVESTOCK TO ACHIEVE SUSTAINABLE FOOD HOUSES IN THE VILLAGE OF BANYU URIP, LOMBOK TENGAH. A service activity that is integrating of plantations, livestock and fisheries to realize a sustainable food house has been carried out. Banyu Urip Village is one of the villages in Gerung Subdistrict, West Lombok regency with the majority of the population as farmers and breeders. Almost every family head in the village of Banyu Urip has large yard and has not been used optimally. The use of land is needed as a source of food and family income through sustainable food house. Sustainable food house can be realized by integrating the use of home garden as land for planting various types of vegetables and fruits, livestock and fisheries. The method of activity is carried out through socialization and work practice regarding planting vegetables and fruits through horticulture technique, utulization of livestock manure as compost and household scale tilapia cultivation. The target partners of the activity are farmer group, family welfare group and student group, while the implemanting partners are some agent of Agricultural Service of Lombok Barat Regency. Integration of plantations, livestock and fisheries are expected to be able to fulfill their daily needs, moreover to improve community welfare.